2005
DOI: 10.1002/bem.20120
|View full text |Cite
|
Sign up to set email alerts
|

Use of the z‐transform to investigate nanopulse penetration of biological matter

Abstract: Short duration, fast rise time electromagnetic ultra-wideband (UWB) pulses ("nanopulses") are generated by numerous electronic devices. Many new technologies involving nanopulses are under development and expected to become widely available soon. Study of nanopulse bioeffects therefore is needed to ensure human safety and to probe the useful range of nanopulses in possible biomedical and biotechnological applications. In this article, we present a new approximation of the Cole-Cole expression for the frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…In this context we have also investigated nanopulse production [Sunkam et al, 2005] and computational approaches to characterizing nanopulse propagation in biological matter Su et al, 2005]. Three broad classes of model have been selected for experimental study: macromolecules (manuscript in preparation), proliferative cells [Dorsey et al, 2005;Sylvester et al, 2005] and non-proliferative cells (manuscript in preparation), and whole organisms (the present report).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context we have also investigated nanopulse production [Sunkam et al, 2005] and computational approaches to characterizing nanopulse propagation in biological matter Su et al, 2005]. Three broad classes of model have been selected for experimental study: macromolecules (manuscript in preparation), proliferative cells [Dorsey et al, 2005;Sylvester et al, 2005] and non-proliferative cells (manuscript in preparation), and whole organisms (the present report).…”
Section: Discussionmentioning
confidence: 99%
“…The precise magnitude of the field inside the worms during exposure was not determined experimentally: the length of an animal at adulthood is but 1 mm, the width about 0.1 mm. In separate work [namely Simicevic and Haynie, 2005;Su et al, 2005], we have reported results of computer simulations of nanopulse propagation in biological matter. There is no known inconsistency between the results of the C. elegans experiments reported here and our simulations.…”
Section: Introductionmentioning
confidence: 98%
“…By substituting the bilinear transform where and are one of the , , or components of and at time step , respectively. The key issue is how to obtain a recursive formula to discretize the fractional-order differentiator in (9). We rewrite (9) (13) and then use a th-order polynomial to approximate the fractional-order differentiator as (14) where and 0 1 are the coefficients of the polynomials corresponding to 1 and 1 , respectively.…”
Section: Formulationmentioning
confidence: 99%
“…The key issue is how to obtain a recursive formula to discretize the fractional-order differentiator in (9). We rewrite (9) (13) and then use a th-order polynomial to approximate the fractional-order differentiator as (14) where and 0 1 are the coefficients of the polynomials corresponding to 1 and 1 , respectively. Because the time stable condition of the FDTD approach guarantees that the time growth factor satisfies (15) the region of is 1,1 .…”
Section: Formulationmentioning
confidence: 99%
See 1 more Smart Citation